Focusing on: Translation in World War II - Schippel, Larisa; Richter, Julia; Rozmyslowicz, Tomasz; Kremmel, Stefanie (chronotopos – A Journal of Translation History, 2020)
The editorial addresses working on translation history in times of a pandemic and introduces the issue, and the focus "Translation in World War II". The editors present an extensive bibliography on the state of research on "Translation in World War II" and invite readers to send in projects and publications on this topic. An extended bibliography on the topic will be made available in the future via the Chronotopos website.